أثر ممارسات إدارة الموارد البشرية وأسلوب القيادة على الأداء التنظيمي: الدورالوسيط للثقافة التنظيمية دراسة تطبيقية على الجامعات الخاصة في الشمال الأردنية - Ahmad Nadir Al-'Aqili
Human resource management is closely related to the behavior of employees, their presence and absence, and most importantly, its impact on their productivity, performance, and psychological trends, which is reflected on the performance of the organization and its relationship with the external environment, and their personal goals and objectives. A successful management is one that innovates in finding solutions to the problems resulting from the new transformations and changes that surround the organization and examines all the variables and factors contributing to the advancement of its performance, improvement, and development. Among the most prominent of them is the performance of the human element, as business institutions constantly strive to achieve efficiency, effectiveness and reach their goals by following modern management methods. One of the organization’s most important directions is to build a flexible organizational culture that responds to rapid changes and affects the behavior of employees and their affiliation to serve the goals and aspirations of the organization, because organizational culture has a noticeable impact in shaping employee behaviors, habits and trends in a way that is reflected in their performance levels. However, this study is demonstrating that the Jordanian private universities located in the Northern governorates suffer from a problem in the management of human resources. This may negatively affect the performance of the employees and their commitment, as there has been lacking on independent body that follows their affairs. In addition, the absence of such body draws attention to the defect in the leadership style exhibited in the governorate. The university and the board of directors may affect the performance and commitment of employees, as well as influence its organizational culture. The main objective of this study is to identify the impact of both human resource management practices and leadership style on organizational performance in Jordanian private universities in the northern governorates. The descriptive analytical approach was applied, and questionnaire was used for data collection. From 400 questionnaires distributed to the study sample represented by four private universities in the northern governorates, 347 questionnaires were retrieved, and after deleting the missing values and outliers, the analyzable questionnaires formed 301 items. The data were analyzed using the SPSS and Smart PLS program involving Pearson's correlation coefficient (Pearson) to ascertain the apparent validity of the content of the study by finding the Pearson’s correlation coefficient between each field and its paragraphs and the total, the degree of accuracy and Cronbach’s Alpha to ensure the stability of the study tool and the frequencies and percentages to describe the study sample. Additionally, arithmetic averages and standard deviations were the statistical processors used to analyze the study results. Moreover, the t-test for independent samples (T-test) was used to determine the significance of the differences between the average estimates of the study sample. The study found a set of results, the most important of which is the existence of a role for human resource management practices and leadership style that can predict organizational culture and organizational performance. The variables in this study were able to explain 40.5% of the variation in organizational performance, while the percentage rose to 46% in the presence of organizational culture. The study also indicated that there is a statistically significant impact of human resource management practices and leadership styles on organizational performance. The impact of each of the human resource management practices and leadership style was observed on organizational performance and organizational culture of employees in Jordanian private universities in the Northern governorates. The study recommended the necessity of paying attention to human resources and creating working conditions and methods that contribute to satisfying the needs of individuals. Also, universities need to pay attention to strengthening the role of supervisors by shifting to guidance in finding creative solutions to provide the best educational service.